PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, PROFITABILITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Wahyuni EDT, Risa; Febiola, 2Fiska (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2021)
This study aims to determine how the influence of independent commissioners, audit committees, profitability and institutional ownership on tax avoidance. The object of this research is the manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange in the 2014-2018 period. The method used for the sampling of this study used a purposive sampling method with a total sample of 25 companies. This study uses the SPSS 16 program. Based on the hypothesis test conducted using multiple linear regression analysis at a significance level of 0.05 on all four variables, the results of this study prove that the audit committee and institutional ownership have no effect on tax avoidance, whereas for the independent commissioner variable and profitability has an effect on tax avoidance.